Isolation Enhancement Using a Hybrid Technique in an Eight-Element UWB MIMO Antenna Design - Mchbal, A.; Touhami, N. Amar; Elftouh, H.; Dkiouak, A. (Advanced Electromagnetics, 2020)
A high order multiple input multiple output (MIMO) antenna assembly is designed for Ultra-Wideband (UWB) applications. The antenna configuration is based on a peculiar arrangement of the radiating elements. A defected microstrip structure is also introduced on the feedlines. The use of a novel technique, the so-called ports-shift, is here discussed. In the proposed antenna, a protruded ground branch structure is employed in combination of three parasitic stubs so as to enhance isolation and impedance matching over the UWB frequency band. The results show that the presented antenna exhibits a good impedance matching which is about -10 dB with a high mutual coupling 15 dB, and envelope correlation coefficients (ECC) smaller than 0.15. The antenna also exhibits good diversity gain of about 9.5, and a good efficiency that varied between 56% and 91% and total active reflection coefficient of less than -20 dB. Which makes it a good candidate for UWB applications.